A beauty glue imitating natural stone texture
By using modified nano calcium carbonate, fluorosilane, organic titanium, aluminum compounds and other ingredients in stone curtain wall beauty glue, combined with artificial marble color solidifying agent, the existing beauty glue has solved the single color, poor adhesion and anti-pollution The problem of poor performance has achieved high strength, pollution-resistant and mildew-proof imitation natural stone texture beauty glue, suitable for interior decoration.
Patent Information
- Application Number
- CN202411438145.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-10-15
AI Technical Summary
The existing stone curtain wall beauty glue has problems such as single color, insufficient aesthetics, poor adhesiveness, poor anti-pollution performance, and prone to mildew in high-temperature and high-humidity environments, which is difficult to meet the needs of interior decoration.
Using a cosmetic glue formula that imitates natural stone texture, including α,ω-dihydroxypolydimethylsiloxane, modified nano calcium carbonate, polytrifluoropropylmethylsiloxane, fluoro-containing silane, bonding Force promoters, gas phase silica, catalysts, crosslinkers, copper zirconium phosphate and 2-butyl-1,2-benzisothiazoline-3-one, modified nano-calcium carbonate and organic titanium and aluminum compounds and other ingredients to improve bonding strength, anti-pollution and mildew resistance, and add artificial marble colored texture solidifier to enhance the aesthetics.
It has achieved imitation natural stone texture beauty glue with strong adhesive, anti-pollution and mildew resistance, improved the decoration quality of stone curtain walls, and has excellent bonding strength, anti-pollution performance and anti-mold effect, which is suitable for interior decoration.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to a beauty glue imitating natural stone texture, belonging to the technical field of adhesives. Background Art
[0002] Stone curtain wall is a very popular building interior and exterior wall decoration material in the construction industry in recent years. Especially in home decoration, more and more people choose natural stone facing materials to add color and enrich the texture of the living environment. Natural stone is mostly made of splicing technology to make overall large-scale facings, and splicing gaps are difficult to avoid. This requires beauty glue to seal the edges and fill the gaps, which can not only cover and conceal the gaps, but also effectively seal and beautify the decorative effect to meet the needs of different decoration styles and application scenarios. The stone curtain wall beauty glue currently used in interior decoration, also known as silicone sealant in the industry, still has the problem of relatively single color, too different from the color and texture of natural stone, and insufficient aesthetics. In addition, the stone curtain wall beauty glue also has significant problems such as poor adhesion, poor anti-pollution performance (easy to get dirty when wiping), and easy to mildew in high temperature and high humidity environments. Therefore, the market is in urgent need of beauty glue that can fully overcome the above problems to meet the growing demand for stone curtain walls in the home decoration market.
[0003] Chinese patent CN118272039A discloses a silicone sealant for stone curtain walls and a preparation method. The silicone sealant includes the following raw materials in parts by weight: 70 parts of polyalkylsiloxane, 20 parts of inorganic filler, 5 parts of ultraviolet catalyst, 0.2 parts of fluoroalkylsilane, 6 parts of silane crosslinking agent, 0.5 parts of silane coupling agent, and 0.02 parts of catalyst. The silicone sealant obtained in this patent focuses on the sealing of outdoor stone curtain walls, and has good weather resistance, but poor bonding strength and mildew resistance, and is not suitable for curtain wall caulking for indoor decoration.
[0004] Chinese patent CN108865052A discloses a one-component dealcoholized silicone structural sealant for building curtain walls and its preparation method, which belongs to the field of silicone structural sealants, including: α,ω-dihydroxy polydimethylsiloxane, alkoxy-terminated polydimethylsiloxane, calcium carbonate, fumed silica, plasticizer, carbon black master paste, antioxidant master paste, silane crosslinker, silane coupling agent, titanate complex and organic tin catalyst, antioxidant master paste includes α,ω-dihydroxy polydimethylsiloxane, calcium carbonate and antioxidant, carbon black master paste includes plasticizer and carbon black. The patent adds carbon black, the color of the colloid is black, the appearance is very poor, and it is difficult to use for interior decoration. In addition, the bonding strength of the silicone sealant obtained by the patent is also relatively poor, and the sealing effect is difficult to guarantee.
[0005] From the above, we can see that the beauty glue currently used for indoor stone curtain walls has problems such as single color, lack of aesthetics, poor adhesion, poor anti-pollution performance, and easy mildew in high temperature and high humidity environments. Therefore, the development of a beauty glue with strong adhesion, anti-pollution and anti-mildew that imitates the texture of natural stone will have a very significant effect on improving the decoration quality of home curtain walls. Summary of the invention
[0006] In view of the deficiencies of the above-mentioned prior art, the present invention provides a beauty glue imitating the texture of natural stone to achieve the following invention objectives: to prepare a beauty glue imitating the texture of natural stone with strong adhesion, anti-pollution and anti-mildew.
[0007] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:
[0008] A beauty glue imitating the texture of natural stone, the specific formula of the beauty glue imitating the texture of natural stone is as follows, in parts by weight:
[0009] 90-150 parts of α,ω-dihydroxy polydimethylsiloxane,
[0010] 25~55 parts of modified nano calcium carbonate,
[0011] 8-13 parts of polytrifluoropropylmethylsiloxane,
[0012] 9-15 parts of fluorinated silane,
[0013] Adhesion promoter 5~9 parts,
[0014] 0.5~2 parts of fumed silica,
[0015] Catalyst 0.5~1.2 parts,
[0016] 3~8 parts of cross-linking agent,
[0017] 0.1~0.5 parts of copper zirconium phosphate,
[0018] 0.2-0.6 parts of 2-butyl-1,2-benzisothiazolin-3-one,
[0019] 4-10 parts of artificial marble color fixer;
[0020] The polytrifluoropropylmethylsiloxane has a number average molecular weight of 300-13000 g / mol, a viscosity of 100-8000 mPa·s at 25° C., and an appearance of a transparent to slightly milky viscous liquid;
[0021] The fluorine-containing silane is one of 1H, 1H, 2H, 2H-perfluorooctyltrichlorosilane and tridecafluorooctyltrimethoxysilane;
[0022] The adhesion promoter is one of tetrabutyl titanate, titanium acetylacetonate, titanium glycolate, aluminum hexafluoro-2,4-pentanedione, diisobutylaluminum acetylacetonate, aluminum triacetylacetonate, diisopropyl di(acetylacetonate)aluminate, and aluminum tri(2,2,6,6-tetramethyl-3,5-heptanedione);
[0023] The fumed silica is hydrophobic fumed silica with a particle size of 10 to 100 nm;
[0024] The catalyst is dibutyltin dilaurate;
[0025] The cross-linking agent is one of methyltrimethoxysilane and methyltriethoxysilane;
[0026] The copper zirconium phosphate is a powder with a particle size of 60 to 1000 nm;
[0027] The artificial marble color grain-fixing agent has a viscosity of 200-450 mPa·s at 25°C and an appearance of a light yellow transparent liquid;
[0028] The following are further improvements to the above technical solution:
[0029] Step 1: Preparation of modified nano calcium carbonate
[0030] Adding a mixed solution of nano calcium carbonate, isooctyl phosphate, n-propanol and water into a dispersion reactor, dispersing at a high speed of 9000-13000 rpm for 6-13 hours, stopping the dispersion, starting stirring, controlling the stirring speed at 2000-4000 rpm, adding a modifier, and then heating to 70-95° C., stirring and reacting under condensation reflux for 11-18 hours, cooling to room temperature, centrifuging, washing the solid obtained by centrifugation with anhydrous ethanol for 3-5 times, putting it into an oven, and drying it at 50-75° C. for 3-7 hours to obtain modified nano calcium carbonate;
[0031] The modifier is one of bis(diethyl citrate) dipropoxide zirconium and bis(diethyl citrate) dipropoxy zirconium chelate;
[0032] The particle size of the nano calcium carbonate is 10-50 nm;
[0033] The mixed solution of n-propanol and water, the mass ratio of n-propanol to water is 6-15:1;
[0034] The mass ratio of the nano calcium carbonate, isooctyl phosphate, a mixed solution of n-propanol and water, and the modifier is 15-35:1-4:150-190:4-10.
[0035] Step 2: Preparation of beauty glue
[0036] According to the specific formula of the beauty glue imitating the texture of natural stone, in parts by weight, α, ω-dihydroxy polydimethylsiloxane, polytrifluoropropyl methylsiloxane, fluorine-containing silane, adhesion promoter, catalyst, crosslinking agent, 2-butyl-1,2-benzisothiazolin-3-one, artificial marble color fixative and fumed silica are added into a dispersion kettle which has been evacuated in advance and protected by dry nitrogen. After high-speed dispersion for 3 to 7 hours at a dispersion rate of 9000 to 13000 rpm, modified nano calcium carbonate and copper zirconium phosphate are added, and the dispersion is continued for 5 to 8 hours. The material is discharged and filled, and sealed with nitrogen to obtain the beauty glue imitating the texture of natural stone.
[0037] Compared with the prior art, the present invention achieves the following beneficial effects:
[0038] 1. The present invention uses isooctyl phosphate as a dispersant to disperse nano calcium carbonate into a mixture of n-propanol and water, and uses bis(diethyl citrate) dipropoxide zirconium and bis(diethyl citrate) dipropoxy zirconium chelate to modify the surface of the nano calcium carbonate, so that the hydroxyl groups on the surface of the nano calcium carbonate are converted into hydrophobic groups, which is very beneficial to the uniformity of dispersion of the nano calcium carbonate in the beauty glue. The nano calcium carbonate can achieve a nano-level uniform dispersion, so that the reinforcing and toughening effect of the nano calcium carbonate on the organic silica gel can be maximized, and the mechanical strength of the beauty glue after curing can be greatly improved;
[0039] 2. The polytrifluoropropylmethylsiloxane, 1H,1H,2H,2H-perfluorooctyltrichlorosilane or tridecafluorooctyltrimethoxysilane added in the present invention, these three fluorine-containing substances contain very active reactive functional groups, which can improve the adhesive properties and mechanical properties of the silicone beauty glue. At the same time, because they contain a large number of fluorine atoms, they can give the colloid excellent pollution resistance;
[0040] 3. The organic titanium compound and organic aluminum compound added in the present invention are used as adhesion promoters, and have very active hydrolysis reaction activity. They can undergo extremely rapid hydrolysis reaction on the surface to be bonded, such as metal, stone, plastic, etc., which contains trace water or hydroxyl functional groups. During this reaction process, the bonding strength between the colloid and the bonded surface can be rapidly improved, and after curing, the beauty glue will have very good bonding strength. At the same time, the rapid hydrolysis reaction can also increase the deep curing rate of the glue layer, thereby improving the overall curing and cross-linking effect of the colloid, and improving the overall mechanical properties of the colloid after curing;
[0041] 4. The present invention achieves long-lasting, stable and efficient anti-mildew performance of the beauty glue by adding two anti-mildew agents, 2-butyl-1,2-benzisothiazolin-3-one and copper zirconium phosphate. 2-butyl-1,2-benzisothiazolin-3-one is an organic anti-mildew agent with high thermal stability, and has very good compatibility with the beauty glue matrix, and can give the beauty glue a very uniform anti-mildew performance as a whole. Copper zirconium phosphate is a powdered inorganic anti-mildew agent, and its anti-mildew performance is long-lasting, non-attenuated and highly efficient. After being effectively dispersed in the beauty glue matrix, the copper zirconium phosphate has a very high copper content, and the high content of copper gives the copper zirconium phosphate very excellent anti-mildew performance. Therefore, the beauty glue with copper zirconium phosphate evenly distributed from the inside to the outside surface will also have very excellent and long-lasting anti-mildew performance.
[0042] 5. The present invention adds artificial marble color texture fixing agent to give the beauty glue the effect of imitating natural stone texture, thereby improving the beauty and texture of the beauty glue in the field of stone curtain wall use;
[0043] 6. The beauty glue imitating the natural stone texture obtained by the present invention has a tensile bonding strength of 3.27-3.64 MPa at 23°C, a bonding damage area of 0%, a surface drying time of 12-16 min, a curing speed of 8.5-9.7 mm / 24 h, a tensile strength of 3.83-4.39 MPa at 23°C, 2.72-3.26 MPa at -40°C, a Shore hardness of 50-57 at 23°C, 58-61 at -40°C, an extrusion property of 2.9-3.6 s, and anti-fouling performance: the pollution width and pollution depth are both 0 mm. When used on the surface of stone and aluminum plates, there is no pollution for 1 month, 3 months, and 6 months, and the mildew resistance level is 0 for 30 days, 60 days, 120 days, 180 days, and 360 days. DETAILED DESCRIPTION
[0044] The preferred embodiments of the present invention are described below. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0045] Embodiment 1: A beauty gel imitating the texture of natural stone
[0046] Step 1: Preparation of modified nano calcium carbonate
[0047] Adding a mixed solution of nano calcium carbonate, isooctyl phosphate, n-propanol and water into a dispersion reaction kettle, dispersing at a high speed of 11000 rpm for 9 hours, stopping the dispersion, starting stirring, adding a modifier while controlling the stirring speed at 2800 rpm, heating to 90°C, stirring and reacting for 17 hours under condensation reflux, cooling to room temperature, centrifuging, washing the solid obtained by centrifugation with anhydrous ethanol for 4 times, putting it into an oven, and drying it at 60°C for 6 hours to obtain modified nano calcium carbonate;
[0048] The modifier is bis(diethylcitrate) zirconium dipropoxide;
[0049] The particle size of the nano calcium carbonate is 40 nm;
[0050] The mixed solution of n-propanol and water, the mass ratio of n-propanol to water is 10:1;
[0051] The mass ratio of the nano calcium carbonate, isooctyl phosphate, a mixed solution of n-propanol and water, and the modifier is 20:3:165:7.
[0052] Step 2: Preparation of beauty glue
[0053] 110 parts of α,ω-dihydroxy polydimethylsiloxane,
[0054] 45 parts of modified nano calcium carbonate,
[0055] 11 parts of polytrifluoropropylmethylsiloxane,
[0056] 13 parts of fluorine-containing silane,
[0057] Adhesion promoter 8 parts,
[0058] 1 part of fumed silica,
[0059] 1 part of catalyst,
[0060] 5 parts of cross-linking agent,
[0061] 0.2 parts of copper zirconium phosphate,
[0062] 0.5 parts of 2-butyl-1,2-benzisothiazolin-3-one,
[0063] 7 parts of artificial marble color fixer;
[0064] The polytrifluoropropylmethylsiloxane has a number average molecular weight of 8000 g / mol, a viscosity of 3000 mPa·s at 25° C., and an appearance of a transparent to slightly milky viscous liquid;
[0065] The fluorine-containing silane is 1H,1H,2H,2H-perfluorooctyltrichlorosilane;
[0066] The adhesion promoter is tetrabutyl titanate;
[0067] The fumed silica is hydrophobic fumed silica with a particle size of 60 nm;
[0068] The catalyst is dibutyltin dilaurate;
[0069] The cross-linking agent is methyltrimethoxysilane;
[0070] The copper zirconium phosphate is a powder with a particle size of 200 nm;
[0071] The artificial marble color grain-fixing agent has a viscosity of 300 mPa·s at 25°C and an appearance of a light yellow transparent liquid;
[0072] According to the specific formula of the beauty glue imitating the texture of natural stone, in parts by weight, α, ω-dihydroxy polydimethylsiloxane, polytrifluoropropyl methylsiloxane, fluorine-containing silane, adhesion promoter, catalyst, cross-linking agent, 2-butyl-1,2-benzisothiazolin-3-one, artificial marble color fixative and fumed silica are added into a dispersion kettle which has been evacuated in advance and protected by dry nitrogen. After high-speed dispersion at a dispersion rate of 11,000 rpm for 6 hours, modified nano calcium carbonate and copper zirconium phosphate are added, and the dispersion is continued for 6 hours. The material is discharged and filled, and sealed with nitrogen to obtain the beauty glue imitating the texture of natural stone.
[0073] Embodiment 2: A beauty gel imitating the texture of natural stone
[0074] Step 1: Preparation of modified nano calcium carbonate
[0075] Adding a mixed solution of nano calcium carbonate, isooctyl phosphate, n-propanol and water into a dispersion reaction kettle, dispersing at a high speed for 6 hours at a speed of 9000 rpm, stopping the dispersion, starting the stirring, adding the modifier while controlling the stirring speed at 2000 rpm, heating to 70°C, stirring and reacting for 11 hours under condensation reflux, cooling to room temperature, centrifuging, washing the solid obtained by centrifugation with anhydrous ethanol for 3 times, putting it into an oven, and drying it at 50°C for 3 hours to obtain modified nano calcium carbonate;
[0076] The modifier is bis(diethyl citrate) dipropoxy zirconium chelate;
[0077] The particle size of the nano calcium carbonate is 10 nm;
[0078] The mixed solution of n-propanol and water, the mass ratio of n-propanol to water is 6:1;
[0079] The mass ratio of the nano calcium carbonate, isooctyl phosphate, a mixed solution of n-propanol and water, and the modifier is 15:1:150:4.
[0080] Step 2: Preparation of beauty glue
[0081] 90 parts of α,ω-dihydroxy polydimethylsiloxane,
[0082] 25 parts of modified nano calcium carbonate,
[0083] 8 parts of polytrifluoropropylmethylsiloxane,
[0084] 9 parts of fluorinated silane,
[0085] Adhesion promoter 5 parts,
[0086] 0.5 parts of fumed silica,
[0087] 0.5 parts of catalyst,
[0088] 3 parts of cross-linking agent,
[0089] 0.1 parts of copper zirconium phosphate,
[0090] 0.2 parts of 2-butyl-1,2-benzisothiazolin-3-one,
[0091] 4 parts of artificial marble color fixer;
[0092] The polytrifluoropropylmethylsiloxane has a number average molecular weight of 300 g / mol, a viscosity of 100 mPa·s at 25° C., and an appearance of a transparent to slightly milky viscous liquid;
[0093] The fluorine-containing silane is tridecafluorooctyltrimethoxysilane;
[0094] The adhesion promoter is titanium acetylacetonate;
[0095] The fumed silica is hydrophobic fumed silica with a particle size of 10 nm;
[0096] The catalyst is dibutyltin dilaurate;
[0097] The cross-linking agent is methyltriethoxysilane;
[0098] The copper zirconium phosphate is a powder with a particle size of 60 nm;
[0099] The artificial marble color grain-fixing agent has a viscosity of 200 mPa·s at 25°C and an appearance of a light yellow transparent liquid;
[0100] According to the specific formula of the beauty glue imitating the texture of natural stone, in parts by weight, α, ω-dihydroxy polydimethylsiloxane, polytrifluoropropyl methylsiloxane, fluorine-containing silane, adhesion promoter, catalyst, crosslinking agent, 2-butyl-1,2-benzisothiazolin-3-one, artificial marble color fixative and fumed silica are added into a dispersion kettle which has been evacuated in advance and protected by dry nitrogen. After high-speed dispersion at a dispersion rate of 9000 rpm for 3 hours, modified nano calcium carbonate and copper zirconium phosphate are added, and the dispersion is continued for 5 hours. The material is discharged and filled, and sealed with nitrogen to obtain the beauty glue imitating the texture of natural stone.
[0101] Embodiment 3: A beauty gel imitating the texture of natural stone
[0102] Step 1: Preparation of modified nano calcium carbonate
[0103] Adding a mixed solution of nano calcium carbonate, isooctyl phosphate, n-propanol and water into a dispersion reaction kettle, dispersing at a high speed for 13 hours at a speed of 13000 rpm, stopping the dispersion, starting stirring, adding a modifier while controlling the stirring speed at 4000 rpm, heating to 95° C., stirring and reacting for 18 hours under condensation reflux, cooling to room temperature, centrifuging, washing the solid obtained by centrifugation with anhydrous ethanol for 5 times, putting it into an oven, and drying it at 75° C. for 7 hours to obtain modified nano calcium carbonate;
[0104] The modifier is bis(diethylcitrate) zirconium dipropoxide;
[0105] The particle size of the nano calcium carbonate is 50 nm;
[0106] The mixed solution of n-propanol and water, the mass ratio of n-propanol to water is 15:1;
[0107] The mass ratio of the nano calcium carbonate, isooctyl phosphate, a mixed solution of n-propanol and water, and the modifier is 35:4:190:10.
[0108] Step 2: Preparation of beauty glue
[0109] 150 parts of α,ω-dihydroxy polydimethylsiloxane,
[0110] 55 parts of modified nano calcium carbonate,
[0111] 13 parts of polytrifluoropropylmethylsiloxane,
[0112] 15 parts of fluorine-containing silane,
[0113] Adhesion promoter 9 parts,
[0114] 2 parts of fumed silica,
[0115] 1.2 parts of catalyst,
[0116] 8 parts of cross-linking agent,
[0117] 0.5 parts of copper zirconium phosphate,
[0118] 0.6 parts of 2-butyl-1,2-benzisothiazolin-3-one,
[0119] 10 parts of artificial marble color fixer;
[0120] The polytrifluoropropylmethylsiloxane has a number average molecular weight of 13000 g / mol, a viscosity of 8000 mPa·s at 25° C., and an appearance of a transparent to slightly milky viscous liquid;
[0121] The fluorine-containing silane is 1H,1H,2H,2H-perfluorooctyltrichlorosilane;
[0122] The adhesion promoter is titanium glycolate;
[0123] The fumed silica is hydrophobic fumed silica with a particle size of 100 nm;
[0124] The catalyst is dibutyltin dilaurate;
[0125] The cross-linking agent is methyltriethoxysilane;
[0126] The copper zirconium phosphate is a powder with a particle size of 1000 nm;
[0127] The artificial marble color grain-fixing agent has a viscosity of 450 mPa·s at 25°C and an appearance of a light yellow transparent liquid;
[0128] According to the specific formula of the beauty glue imitating the texture of natural stone, in parts by weight, α, ω-dihydroxy polydimethylsiloxane, polytrifluoropropyl methylsiloxane, fluorine-containing silane, adhesion promoter, catalyst, crosslinking agent, 2-butyl-1,2-benzisothiazolin-3-one, artificial marble color fixative and fumed silica are added into a dispersion kettle which has been evacuated in advance and protected by dry nitrogen. After high-speed dispersion at a dispersion rate of 13,000 rpm for 7 hours, modified nano calcium carbonate and copper zirconium phosphate are added, and the dispersion is continued for 8 hours. The material is discharged and filled, and sealed with nitrogen to obtain the beauty glue imitating the texture of natural stone.
[0129] Embodiment 4: A beauty gel imitating the texture of natural stone
[0130] The operation of step 1 is the same as that of embodiment 1;
[0131] Step 2: Preparation of beauty glue
[0132] The adhesion promoter is aluminum hexafluoro-2,4-pentanedione;
[0133] The other operations are the same as those in Example 1.
[0134] Embodiment 5: A beauty gel imitating the texture of natural stone
[0135] The operation of step 1 is the same as that of embodiment 1;
[0136] Step 2: Preparation of beauty glue
[0137] The adhesion promoter is diisobutylaluminum acetylacetonate complex;
[0138] The other operations are the same as those in Example 1.
[0139] Embodiment 6: A beauty gel imitating the texture of natural stone
[0140] The operation of step 1 is the same as that of embodiment 1;
[0141] Step 2: Preparation of beauty glue
[0142] The adhesion promoter is aluminum triacetylacetonate;
[0143] The other operations are the same as those in Example 1.
[0144] Example 7: A beauty gel imitating the texture of natural stone
[0145] The operation of step 1 is the same as that of embodiment 1;
[0146] Step 2: Preparation of beauty glue
[0147] The adhesion promoter is diisopropyl di(acetylacetonato)aluminate;
[0148] The other operations are the same as those in Example 1.
[0149] Embodiment 8: A beauty gel imitating the texture of natural stone
[0150] The operation of step 1 is the same as that of embodiment 1;
[0151] Step 2: Preparation of beauty glue
[0152] The adhesion promoter is tris(2,2,6,6-tetramethyl-3,5-heptanedione)aluminum;
[0153] The other operations are the same as those in Example 1.
[0154] Comparative Example 1: Based on Example 1, step 1, preparation of modified nano-calcium carbonate, is not performed. In step 2, preparation of beauty glue, 45 parts of modified nano-calcium carbonate are replaced by 45 parts of nano-calcium carbonate. The specific operation is as follows:
[0155] Step 1, preparation of modified nano calcium carbonate is not performed;
[0156] Step 2: Preparation of beauty glue
[0157] Replace 45 parts of modified nano calcium carbonate with 45 parts of nano calcium carbonate.
[0158] Same as Example 1.
[0159] Comparative Example 2: Based on Example 1, in step 2, in the preparation of the beauty glue, no polytrifluoropropylmethylsiloxane and fluorine-containing silane are added, and 11 parts of polytrifluoropropylmethylsiloxane and 13 parts of fluorine-containing silane are replaced by 24 parts of α,ω-dihydroxypolydimethylsiloxane in equal amounts. The specific operation is as follows:
[0160] The operation of step 1 is the same as that of embodiment 1;
[0161] Step 2: Preparation of beauty glue
[0162] The 11 parts of polytrifluoropropylmethylsiloxane and 13 parts of fluorine-containing silane were replaced by 24 parts of α,ω-dihydroxypolydimethylsiloxane in equal amounts, and the other operations were the same as in Example 1.
[0163] Comparative Example 3: Based on Example 1, in step 2, in the preparation of the beauty glue, no adhesion promoter is added, and 8 parts of the adhesion promoter are replaced by 8 parts of α, ω-dihydroxy polydimethylsiloxane in equal amounts. The specific operation is as follows:
[0164] The operation of step 1 is the same as that of embodiment 1;
[0165] Step 2: Preparation of beauty glue
[0166] The other operations were the same as in Example 1 except that 8 parts of the adhesion promoter were replaced by 8 parts of α,ω-dihydroxypolydimethylsiloxane.
[0167] Performance Testing:
[0168] The following performance tests were performed on the beauty gels imitating natural stone textures obtained in Examples 1, 2, 3, 4, 5, 6, 7, 8 and Comparative Examples 1, 2, 3:
[0169] 1. Tensile adhesion: Refer to GB / T16776-2005 to test the tensile adhesion strength and adhesion failure area at 23°C;
[0170] 2. Surface drying time: refer to GB / T13477.3-2017 test;
[0171] 3. Curing speed: refer to GB / T13477.3-2017 test;
[0172] 4. Tensile strength: Refer to GB / T528-2009 to test the tensile strength at 23℃ and -40℃;
[0173] 5. Shore hardness: Refer to GB / T531.1-2008 to test the Shore hardness at 23℃ and -40℃;
[0174] 6. Extrusion: Refer to GB16776-2005 to test extrusion to evaluate the construction performance of the beauty glue;
[0175] 7. Anti-pollution performance: The penetration pollution test of porous substrates is carried out in accordance with GB / T 23261-2009; the vertical flow pollution test is used to characterize the self-cleaning ability of the beauty glue. The test substrates are selected from stone and aluminum plate surfaces. The pollution levels are divided from light to heavy into no pollution, basically no pollution, pollution, and obvious pollution;
[0176] 8. Mildew resistance level: Tested at 30°C and 60% relative humidity according to JC / T885-2016 and GB / T 1741-2020;
[0177] The specific test results are shown in Table 1:
[0178] Table 1
[0179]
[0180]
[0181] From the data in Table 1, it can be seen that in Comparative Example 1 where the nano calcium carbonate is not surface modified, the tensile bonding strength is nearly half lower than that in Example 1, the bonding failure area is greatly increased to 29%, the surface drying time is slowed down by 10 minutes, the curing speed is reduced to 5.1 mm / 24 h, the tensile strength is reduced to the lowest value among all the embodiments and comparative examples, the Shore hardness is increased to the highest value among all the embodiments and comparative examples, the extrudability is increased to 9.5 s, which is the worst value among all the embodiments and comparative examples, and the anti-pollution level is also significantly reduced. This shows that the nano calcium carbonate is not surface modified, and the large number of hydroxyl groups on the surface of the nano calcium carbonate makes it very easy to agglomerate, and it is difficult to obtain nanoscale inside the organic silica gel. The dispersion uniformity of the beauty glue is greatly reduced, which leads to a comprehensive and substantial reduction in almost all performance indicators of the beauty glue. It can be seen that nano calcium carbonate can be uniformly dispersed at nanometer scale in the organic silica gel after surface modification by bis(diethyl citrate) dipropoxide zirconium and bis(diethyl citrate) dipropoxy zirconium chelate under the dispersing effect of isooctyl phosphate, thereby greatly improving the various properties of the beauty glue. In Comparative Example 2, polytrifluoropropyl methylsiloxane and fluorinated silane are not added. The tensile bonding strength of Comparative Example 2 is much worse than that of Example 1. Compared with Comparative Example 1, the bonding performance is also reduced, the surface drying time is prolonged, the curing speed is slowed down, the tensile strength is significantly reduced, the Shore hardness is increased, and the extrusion performance is significantly reduced. The anti-pollution performance is low, and the anti-pollution performance is reduced to the lowest value among all the embodiments and comparative examples. This shows that polytrifluoropropylmethylsiloxane and fluorine-containing silane can not only effectively improve the mechanical properties of organic silicone such as bonding strength, tensile strength, and Shore hardness, but also improve the indicators of reaction performance such as surface drying time and curing speed. More importantly, polytrifluoropropylmethylsiloxane and fluorine-containing silane have a very significant effect on improving the anti-pollution performance of the beauty glue. This shows that the above two fluorine-containing siloxanes or silane-like substances not only have very reactive functional groups to promote the bonding and curing of organic silicone, but also have very good anti-pollution performance due to the presence of fluorine element; Comparative Example 3 does not add adhesive force to promote The adhesion promoter plays a vital role in improving the adhesion performance of the colloid. In addition, it also greatly improves the mechanical properties of the colloid, but has no effect on the anti-pollution performance. The mildew resistance grades of all embodiments and all comparative examples are very excellent, and the long-lasting effectiveness of the mildew resistance is also very uniform. During the test period of nearly one year, there is no attenuation of the mildew resistance, which shows that 2-butyl-1,2-benzisothiazolin-3-one and copper zirconium phosphate can provide a long-lasting and effective mildew resistance for the beauty glue.
[0182] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A beauty glue imitating the texture of natural stone, characterized by: The specific formula of the beauty gel imitating the texture of natural stone is as follows, in parts by weight: 90-150 parts of α,ω-dihydroxy polydimethylsiloxane, 25~55 parts of modified nano calcium carbonate, 8-13 parts of polytrifluoropropylmethylsiloxane, 9-15 parts of fluorinated silane, Adhesion promoter 5~9 parts, 0.5~2 parts of fumed silica, Catalyst 0.5~1.2 parts, 3~8 parts of cross-linking agent, 0.1~0.5 parts of copper zirconium phosphate, 0.2-0.6 parts of 2-butyl-1,2-benzisothiazolin-3-one, 4-10 parts of artificial marble color fixer; The modified nano calcium carbonate has a preparation method comprising: adding a mixed solution of nano calcium carbonate, isooctyl phosphate, n-propanol and water into a dispersion reaction kettle, dispersing at a speed of 9000-13000 rpm for 6-13 hours, stopping the dispersion, starting the stirring, controlling the stirring speed at 2000-4000 rpm, adding a modifier, heating to 70-95°C, stirring and reacting for 11-18 hours under condensation reflux, cooling to room temperature, centrifuging, washing the solid obtained by centrifugation with anhydrous ethanol for 3-5 times, putting it into an oven, and drying it at 50-75°C for 3-7 hours to obtain the modified nano calcium carbonate; The modifier is one of bis(diethyl citrate) dipropoxide zirconium and bis(diethyl citrate) dipropoxy zirconium chelate; The polytrifluoropropylmethylsiloxane has a number average molecular weight of 300-13000 g / mol, a viscosity of 100-8000 mPa·s at 25° C., and an appearance of a transparent to slightly milky viscous liquid; The fluorine-containing silane is one of 1H, 1H, 2H, 2H-perfluorooctyltrichlorosilane and tridecafluorooctyltrimethoxysilane; The adhesion promoter is one of tetrabutyl titanate, titanium acetylacetonate, titanium glycolate, aluminum hexafluoro-2,4-pentanedione, diisobutylaluminum acetylacetonate, aluminum triacetylacetonate, diisopropyl di(acetylacetonate)aluminate, and aluminum tri(2,2,6,6-tetramethyl-3,5-heptanedione); The fumed silica is hydrophobic fumed silica with a particle size of 10 to 100 nm; The catalyst is dibutyltin dilaurate; The cross-linking agent is one of methyltrimethoxysilane and methyltriethoxysilane; The copper zirconium phosphate is a powder with a particle size of 60 to 1000 nm; The artificial marble color grain-fixing agent has a viscosity of 200-450 mPa·s at 25° C. and an appearance of a light yellow transparent liquid.
2. The beauty glue imitating natural stone texture according to claim 1, characterized in that: The particle size of the nano calcium carbonate is 10-50 nm; The mixed solution of n-propanol and water, the mass ratio of n-propanol to water is 6-15:1; The mass ratio of the nano calcium carbonate, isooctyl phosphate, a mixed solution of n-propanol and water, and the modifier is 15-35:1-4:150-190:4-10.
3. The beauty glue imitating natural stone texture according to claim 1, characterized in that: The preparation method of the beauty glue is as follows: according to the specific formula of the beauty glue imitating the texture of natural stone, in parts by weight, α,ω-dihydroxy polydimethylsiloxane, polytrifluoropropyl methylsiloxane, fluorine-containing silane, adhesion promoter, catalyst, crosslinking agent, 2-butyl-1,2-benzisothiazolin-3-one, artificial marble color fixer and fumed silica are added into a dispersion kettle which has been evacuated in advance and is protected by dry nitrogen, and after high-speed dispersion for 3-7 hours at a dispersion rate of 9000-13000 rpm, modified nano calcium carbonate and copper zirconium phosphate are added, and the dispersion is continued for 5-8 hours, and the material is discharged and filled, and sealed with nitrogen to obtain the beauty glue imitating the texture of natural stone.